ASSESSMENT OF LEVELS AND ASSOCIATED RISKS OF EXPOSURE TO VOCS RELEASED FROM MSW LANDFILL SITES - Demir, Selami; Saral, Arslan; Kuzu, S. Levent (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2012)
A modeling study was performed to simulate atmospheric dispersion of volatile organic compound (VOC) emissions from a main municipal, solid waste (MSW) landfill site in Istanbul-Turkey using Industrial Source Complex short term version (ISCST3). Ambient concentrations of 1,2-dichloroethane, dichloromethane, benzene, vinyl chloride, toluene, xylenes and dichlorobenzenes emitted from the landfill site were calculated over six averaging periods (1, 2, 4, 8, 12 and 24 hours). Real case model results and worst case scenario-based model results were obtained for each VOC and over each averaging periods. The model results were combined with human activity data in order to estimate average community exposure levels to landfill VOCs and associated risks. For instance, those values for dichloromethane over twelve hours of exposure duration were 0.910 mu g.hr.m(-3) and 2.0*10(-9), respectively. For worst case conditions, these values were estimated as 2.249 mu g.hr.m(-3) and 4.35 * 10(-8). Values for each and all VOC species over each averaging period were evaluated. No significant health risks associated with exposure to landfill VOCs were expected.
Keywords: Istanbul; Landfill VOC; Dispersion modeling; Exposure; Probability analysis; VOLATILE ORGANIC-COMPOUNDS; TURKEY; CHINA; Environmental Sciences & Ecology